Improving Students’ Writing Ability Through The Use Of Instagram Caption - Diana Yesi Prastiwi (Universitas Muria Kudus, 2021)
This study aims to improve the students’ writing ability of ten grade in vocational high school Manbaul Huda Pati through the use of Instagram caption. This research is motivated by students’ anxiety in learning English, especialy writing. The purpose of this study is to know how is Instagram caption as a media applied and improve students writing skill. The subject of this study was 27 students in X TBSM of SMK Manbaul Huda Pati. The study used classroom research design. In this study, the researcher used Instagram caption because social media is closer to students so it will be easier to apply it in learning activities. In this case, the media was used to attract students in writing English in the class. There are several steps in this research, namely: pre-elimination test, conducting the cycles starting with planning, acting, observing, reflecting, and post-test. The result of the study showed that there were improvements of students’ writing ability after being taught using Instagram caption as a media. It was proved by the improvement between the students’ score of preliminary test and cycle 2 post-test. The average of preliminary test was 68.89, while the average of cycle 2 post-test was 79.81. Based on the result above, it can be concluded that this media gave positive contribution to the improvement of the students’ writing ability. This media is beneficial to help the students to learn writing English in more enjoyable way.